Thermalisme et villégiature autour d’Auch - Anaïs Comet (Les Cahiers de Framespa)
Around Auch, in the mid-19th century, several hot springs were exploited. Small thermal establishments were set up there, but not all of them gave rise to real spas as in Castéra-Verduzan. The traces of thermalism are nevertheless clearly visible around the sites of Maska (Castéra-Verduzan) and Fontaine-Chaude (Lavardens), or even La Quèque and Enbernelli (Castelnau-Barbarens). The comparison carried out at the scale of the five sites allows to identify common characteristics, whatever the extent of the thermal activity. These common features are mainly found in the architecture. Notable differences appear very quickly between these sites, in particular concerning the curists who frequent them or the holiday offer which is proposed to them.